2017
DOI: 10.4103/1008-682x.177842
|View full text |Cite
|
Sign up to set email alerts
|

The effect of flutamide on the physical working capacity and activity of some of the key enzymes for the energy supply in adult rats

Abstract: The aim of the study was to assess the effects of androgen receptor antagonists on the physical working capacity and activity of some of the key muscle enzymes for the energy supply in rats. Young adult male Wistar rats were divided into two groups. One group received 15 mg kg−1 of flutamide daily for 6 days a week and the other group served as control for 8 weeks. At the beginning and at the end of the experiment, all rats were subjected to submaximal running endurance (SRE), maximum time to exhaustion (MTE),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 32 publications
3
8
0
Order By: Relevance
“…In addition, flutamide is considered to inhibit AR singling through blocking AR's binding to its ligand like testosterone or dihydrotestosterone [29] , and in the current study flutamide was found to reverse the training-induced increases of AR in muscles, suggested that flutamide might inhibit AR signaling through down-regulating the protein level of AR in tissue, except for the well-known blockade of binding with testosterone. Similar result was reported by a recent study which revealed the inhibitive function of flutamide by down-regulating AR protein in tissues [10] .…”
Section: Crucial Effects Of Ar In Training-induced Selective Muscle Hsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, flutamide is considered to inhibit AR singling through blocking AR's binding to its ligand like testosterone or dihydrotestosterone [29] , and in the current study flutamide was found to reverse the training-induced increases of AR in muscles, suggested that flutamide might inhibit AR signaling through down-regulating the protein level of AR in tissue, except for the well-known blockade of binding with testosterone. Similar result was reported by a recent study which revealed the inhibitive function of flutamide by down-regulating AR protein in tissues [10] .…”
Section: Crucial Effects Of Ar In Training-induced Selective Muscle Hsupporting
confidence: 91%
“…But most of the reports about AR's role were focused on the sedentary participants. At training state, AR was likely to be very important not only for muscle hypertrophy but also strength promotion, for example, the submaximal running endurance and the maximum time to exhaustion were reduced in flutamide-treated rats [10] and in human, the intramuscular AR content influenced the cross-sectional areas of muscle in previously trained men [11] . Although muscle hypertrophy is a vital factor to enhance exercise performance, the roles of AR in exercise-induced muscle hypertrophy are not fully clarified, let alone the underlying molecular mechanisms.…”
Section: Crucial Effects Of Ar In Training-induced Selective Muscle Hmentioning
confidence: 99%
See 1 more Smart Citation
“…But most of the reports about AR's role were focused on the sedentary participants. At training state, AR was likely to be very important not only for muscle hypertrophy but also strength promotion, for example, the submaximal running endurance and the maximum time to exhaustion were reduced in flutamide-treated rats [10] and in human, the intramuscular AR content influenced the cross-sectional areas of muscle in previously trained men [11]. Although muscle hypertrophy is a vital factor to enhance exercise performance, the roles of AR in exercise-induced muscle hypertrophy are not fully clarified, let alone the underlying molecular mechanisms.…”
Section: Flutamide Reversed the Training-induced Selective Increases mentioning
confidence: 99%
“…On the contrary, global AR gene knockout (ARKO) and specific skeletal muscle tissue ARKO mice showed alterations in the muscle mass (such as gastrocnemius, quadriceps and soleus) [5,6], muscle glycogen [7] and exercise performance. The important role of AR in the increases of muscle mass and exercise performance at untrained state was demonstrated [5,[8][9][10][11], but whether AR exerted crucial role in exercise-induced muscle hypertrophy in vivo have not been thoroughly verified. To our best knowledge, until now no ARKO model mice have been used to explore AR's role in exercise-induced changes in muscle mass and performance, moreover, ARKO mice could not be obtained commercially.…”
Section: Introductionmentioning
confidence: 99%